2020
DOI: 10.34172/mj.2020.041
|View full text |Cite
|
Sign up to set email alerts
|

The comparing effects of four-week rock climbing with or without blood flow restriction on vascular endothelial growth factor and Growth Hormone in elite climbers

Abstract: Background: Angiogenesis and increased capillary density of skeletal muscle is one of the potential physiological changes during the flow restriction exercise (BFR). Therefore, the aim of this research was to evaluate the effect of four weeks rock climbing with or without blood flow restriction on vascular endothelial growth factor and Growth Hormone in elite climbers.Methods: In this semi-experimental study, 26 elite climbers (aged 25-30 years; body fat percent 8-14%; 4 years athletic training history) in a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recent research revealed that BFR training can elicit improvements in both strength (Scott et al, 2016) and endurance (Held et al, 2020(Held et al, , 2022 indices. There is already some research on the effects of BFR and climbing (Aghaei et al, 2020;Ebadifar et al, 2021). These studies primarily focus on hormonal responses to BFR training rather than climbing-specific performance adaptations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research revealed that BFR training can elicit improvements in both strength (Scott et al, 2016) and endurance (Held et al, 2020(Held et al, , 2022 indices. There is already some research on the effects of BFR and climbing (Aghaei et al, 2020;Ebadifar et al, 2021). These studies primarily focus on hormonal responses to BFR training rather than climbing-specific performance adaptations.…”
Section: Introductionmentioning
confidence: 99%
“…These studies primarily focus on hormonal responses to BFR training rather than climbing-specific performance adaptations. For example, studies have demonstrated that BFR climbing led to increased basal levels of vascular endothelial growth factors, growth hormones (Aghaei et al, 2020), and testosterone (Ebadifar et al, 2021) during a 4-week intervention trial. Despite these findings, the impact of BFR training on relevant climbing-specific performance indicators remains unknown.…”
Section: Introductionmentioning
confidence: 99%